7T MR neurography‐ultrasound fusion for peripheral nerve imaging. Issue 4 (22nd January 2020) - Schreiber, Stefanie; Schreiber, Frank; Peter, Alica; Isler, Eser; Dörner, Marc; Heinze, Hans‐Jochen; Petri, Suanne; Tempelmann, Claus; Nestor, Peter J.; Grimm, Alexander; Vielhaber, Stefan
Abstract: Background: We present one patient with an initial diagnosis of Guillain‐Barré syndrome (GBS) and one with Charcot–Marie–Tooth disease (CMT) type 1A. Methods: Both patients underwent ankle tibial nerve fusion‐imaging of high‐resolution ultrasound (HRUS) with 7T MR neurography (MRN). Results: In GBS, the nerve was enlarged, T2‐hyperintense, and showed increased vascularization 21 months after symptom onset. In CMT1A, the enlarged nerve was T2‐isointense with normal endoneurial blood flow. Conclusions: We demonstrate the utility of 7T‐MRN‐HRUS‐fusion‐imaging. In GBS, there was evidence of ongoing inflammation resulting in a changed diagnosis to acute‐onset chronic demyelinating polyradiculoneuropathy and maintenance of immunotherapy. By MRN‐HRUS‐fusion, patients with presumed peripheral axonal degeneration could be shown to display imaging markers associated with peripheral nervous system inflammation. Thus, more accurate identification of a treatable inflammatory component may become possible.